Addition of nimotuzumab to concurrent chemoradiotherapy after induction chemotherapy improves outcomes of patients with locally advanced nasopharyngeal carcinoma - Wang, Run-Jie; Ke, Rui-Quan; Yu, Yi-Feng; Lu, Guan-Zhong; Wu, San-Gang (Frontiers in Pharmacology, 2024)
Purpose: To investigate the survival outcomes and toxicities associated with the addition of nimotuzumab to concurrent chemoradiotherapy (CCRT) in locally advanced nasopharyngeal carcinoma (LANPC) patients who received induction chemotherapy (IC).Methods: Patients with stage III-IVA nasopharyngeal carcinoma who received IC and CCRT between January 2017 and October 2021 were retrospectively included. We aimed to compare the locoregional recurrence-free survival (LRFS), distant metastasisfree survival (DMFS), disease-free survival (DFS), and overall survival (OS) between patients treated with CCRT+nimotuzumab and CCRT alone.Results: We included 411 patients in the analysis. Of these patients, 267 (65.0%) and 144 (35.0%) had CCRT+nimotuzumab and CCRT alone, respectively. Similar LRFS was found between those with and without nimotuzumab (92.9% vs. 92.6%, P=0.855).The 3-year DMFS was 88.2% and 76.2% in those with and without nimotuzumab (P=0.002). The 3-year DFS was 83.4% and 70.6% in those with and without nimotuzumab treatment (P=0.003). The 3-year OS was 92.1% and 81.1% in those with and without nimotuzumab (P=0.003). The multivariate Cox regression analysis indicated that the addition of nimotuzumab was independently associated with better DMFS (hazard ratio [HR] 0.606, P=0.049), DFS (HR 0.613, P=0.028), and OS (HR 0.497, P=0.019). No significant differences in major toxicities were found between the two treatment arms, including hematologic toxicities, hepatoxicity, nephrotoxicity, gastrointestinal reactions, and mucositis (all P>0.05).The addition of nimotuzumab to CCRT after IC in LANPC has shown promising results in improving treatment outcomes and acceptable toxicities.